2017
DOI: 10.5539/jsd.v10n2p249
|View full text |Cite
|
Sign up to set email alerts
|

Social and Environmental Impacts on Rural Communities Residing Near the Industrial Complex of Sao Luis Island, State of Maranhão, Brazil

Abstract: The aim of the present study was to analyze the major social and environmental implications of the presence of the industrial district of the city of São Luís (Brazil) over a span of 30 years. The district was established in the 1980s to receive industrial enterprises of the Grande Carajás Program, which led to the installation of a massive support infrastructure. Industrial activities have contributed substantially to rapid, definitive, irreversible changes to the way of life of the population residing near t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2018
2018
2023
2023

Publication Types

Select...
4

Relationship

1
3

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 2 publications
0
3
0
Order By: Relevance
“…The most negative impact was observed on the natural environment. This is possibly linked with the perception of local communities regarding the immediate risks associated with industrial activities in the area (De Castro et al, 2017). However, it should be noted that almost a third of the sample considered that there was no impact from the existence of enterprises.…”
Section: Years Of Educationmentioning
confidence: 98%
“…The most negative impact was observed on the natural environment. This is possibly linked with the perception of local communities regarding the immediate risks associated with industrial activities in the area (De Castro et al, 2017). However, it should be noted that almost a third of the sample considered that there was no impact from the existence of enterprises.…”
Section: Years Of Educationmentioning
confidence: 98%
“…Fish assemblage structure in a port region... Iheringia, Série Zoologia, 108: e2018018 The variation of species richness among the estuaries may be associated to factors such as latitude, seasonal variability, degree of contamination by chemical pollutants and impacts that result from the joint action of several factors such as urbanization, landfills, industrial poles implantation, construction and maintenance of ports (Franca et al, 2011;Pasquaud et al, 2015;Gurdek & Acuña-Plavan, 2017;Castro, et al, 2017). In the specific case of São Marcos Bay, which has the second largest port structure in Brazil, several studies have identified contamination in water and sediments as a result of anthropic activities, including bioaccumulation of contaminants in fish, which may affect marine ecosystems and aquatic organisms (Carvalho-Neta et al, 2012;Sousa et al, 2013;Castro et al, 2018).…”
Section: Discussionmentioning
confidence: 99%
“…Examples include target 8.9 (increased tourism), which can both encourage forest conservation to attract visitors, but also deplete forests to make way for necessary infrastructure and to meet increased demands for forest resources [28]). Similarly, target 9.2 (increased industry and manufacturing), can cause damage through associated infrastructure, pollution and influxes of workers [29], but can also be beneficial if it promotes a shift away from expanding agriculture [30], or if the added value from manufactured products means that less forest products are required to meet harvesters' financial needs [31].…”
Section: Introductionmentioning
confidence: 99%